Stabilitas Sistem Keuangan dan Pertumbuhan Ekonomi Melalui Kebijakan Makroprudensial di 5 Negara ASEAN - Aprillia, Audre; Syahfia, Nurul; Putri, Winsi Fadiah; Nasution, Diwayana Putri; Rusiadi, Rusiadi (LPPM Institut Pendidikan Nusantara Global, 2024)
The objectives of the research include efforts to explore the macroprudential impact on financial system stability (FSS) and economy in 5 (five) ASEAN member countries during the period 2013 to 2019. The methodology of this study is based on the application of the Mutant Method, VAR, and Ardl Panel. Analysis of the research results revealed that the variables Rii Interest Rate (SBR), Money Supply (JUB), Exchange Rate, and Loan to Depocit Ratio (LDR) simultaneously have a significant influence on Gross Domestic Product (GDP). In addition, SBR and JUB have also proven to have an impact on the inflation rate. The results also produced a panel of leading indicators, consisting of the Inflation Index (INF) and currency exchange rates, as a marker of the effectiveness of control variables on economic stability in ASEAN countries. This indicator shows that INF and exchange rates play an important role in controlling economic stability, with controls in the short to long term. These findings provide significant insight into key factors affecting economic stability in the ASEAN region, providing the basis for more effective policy formulation in the future.